High Voltage Insulating Materials-Current State and Prospects - Rozga, Pawel; Beroual, Abderrahmane (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Studies on new solutions in the field of high-voltage insulating materials are presented in this book. Most of these works concern liquid insulation, especially biodegradable ester fluids; however, in a few cases, gaseous and solid insulation are also considered. Both fundamental research as well as research related to industrial applications are described. In addition, experimental techniques aimed at possibly finding new ways of analysing the experimental data are proposed to test dielectrics.